THE TURKISH MODEL AND TURKEY’S CENTRAL ASIAN POLICIES CONDITIONED BY WESTERN STRATEGIC INTERESTS - HOVSEPYAN, Levon (CENTRAL ASIA AND THE CAUCASUS, 2009)
The post-Cold War geopolitical transformations forced the Turkish leaders to revise their foreign policy and national security/defense concepts. The Turkish military-political circles moved away from the narrow ideas of strategy and foreign policy of the former federal security conception to a wider approach of alternative foreign policies. Early in the 1990s Turkey perceived the Caucasus and Central Asia as an alternative foreign policy sphere. It used its ethnic, linguistic, and cultural ties with the Turkic-speaking Central Asian nations to assume a leading role and establish its influence in the region. Turkey’s geopolitical ambitions coincided with the foreign political strategies of the West, the United States in particular. This explains why in the early 1990s Ankara created a new Central Asian strategy: it did not want to miss the chance of becoming a post-Cold War regional power. During the Cold War its NATO membership supplied Turkey with a clearly defined role on the Alliance’s southern flank: it was expected to check the Soviet Union’s infiltration into the Mediterranean and the Middle East.1 During the Cold War Turkey’s foreign policy and national security conceptions perfectly fitted the military-political conception of NATO and the United States in particular. I have already mentioned that the end of the Cold War caused geopolitical transformations that created new foreign policy and security strategies for many countries. In the beginning Ankara was baffled by the vagueness of the new realities and spent some time trying to assess its future foreign and security policies and a new strategy. In the absence of the Soviet Union, Turkey’s geostrategic importance, as seen from the West as whole and the U.S. in particular, became obscure. The end of the Cold War also bred apprehensions among the Turkish political top crust about the country’s security, which forced it to step up the country’s involvement in the Middle East, the Balkans, the Caucasus, and Central Asia.2 Indeed, the country could be deprived of its strategic importance for NATO, which made looking for a new foreign policy strategy oriented toward the newly independent Turkic-speaking Central Asian states indispensable.